Dynamic path planning for reconfigurable rovers using a multi-layered grid - Sánchez Ibáñez, José Ricardo; Pérez-del-Pulgar-Mancebo, Carlos Jesús; Azkarate, Martin; Gerdes, Levin; García-Cerezo, Alfonso José (My University, 2019)
Autonomy on rovers is desirable in order to extend the traversed distance, and therefore, maximize the number of places visited during the mission. It depends heavily on the information that is available for the traversed surface on other planet. This information may come from the vehicle’s sensors as well as from orbital images. Besides, future exploration missions may consider the use of reconfigurable rovers, which are able to execute multiple locomotion modes to better adapt to different terrains. With these considerations, a path planning algorithm based on the Fast Marching Method is proposed. Environment information coming from different sources is used on a grid formed by two layers. First, the Global Layer with a low resolution, but high extension is used to compute the overall path connecting the rover and the desired goal, using a cost function that takes advantage of the rover locomotion modes. Second, the Local Layer with higher resolution but limited distance is used where the path is dynamically repaired because of obstacle presence. Finally, we show simulation and field test results based on several reconfigurable and non-reconfigurable rover prototypes and a experimental terrain.
Keywords: Multicontroladores; Robótica; Path planning; Planetary Exploration; Rover